2019
DOI: 10.1002/ece3.5622
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of marine barriers for genetic diversity of the coral‐specialist yellowbar angelfish from the Northwestern Indian Ocean

Abstract: Ocean circulation, geological history, geographic distance, and seascape heterogeneity play an important role in phylogeography of coral‐dependent fishes. Here, we investigate potential genetic population structure within the yellowbar angelfish (Pomacanthus maculosus) across the Northwestern Indian Ocean (NIO). We then discuss our results with respect to the above abiotic features in order to understand the contemporary distribution of genetic diversity of the species. To do so, restriction site‐associated DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…2017a ). Finally, a study on the yellowbar angelfish, Pomacanthus maculosus , generated a SNP data set with 10,225 SNPs and found that the F ST between the two seas was 0.015 ( Torquato et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…2017a ). Finally, a study on the yellowbar angelfish, Pomacanthus maculosus , generated a SNP data set with 10,225 SNPs and found that the F ST between the two seas was 0.015 ( Torquato et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of IBD in the genetic differentiation of populations was originally illustrated in 1948 (Wright 1943). Since then, IBD has been observed and reported in many population genetic studies, for example, the population genetic studies Nile Tilapia throughout west Africa and the coral-specialist yellowbar angelfish from the Northwestern Indian Ocean, the genetic distances between populations were clearly correlated to their geographic distance (Lind et al 2019, Torquato et al 2019. In this study, the IBD test performed by Mantel tests showed a significant correlation between genetic and geographical distances among L. maculatus populations.…”
Section: Negative Selection In Mitochondrial Protein-coding Genesmentioning
confidence: 99%
“…This result corroborates with previous population genetic studies. For example, phylogeographic investigations on fish species such as Scomberomorus commerson (van Herwerden et al, 2006); Cephalopholis hemistiktos (Priest et al, 2016) and Pomacanthus maculosus (Torquato et al, 2019), used different genetic markers and found a significant discontinuity positioned in southern Oman. Moreover, in our models the strength of this barrier increased when the taxa are spawning during the summer monsoon.…”
Section: Discussionmentioning
confidence: 99%
“…The main hypotheses to explain faunal and genetic differences between both sides of the peninsula usually involve seascape features and/or ocean circulation off Oman (Torquato et al 2019). The seascape is characterized by to coral colonies in southern Omani coast being weakly developed and represented by a reduced number of species (Burt et al, 2016; Sheppard & Salm, 1988), such that the lack of coral-habitat creates an unbridgeable gap for coral-dependent species (Priest et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation